(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
The study focused on the influence of psychological traits on the entrepreneurial intention of business education undergraduates in Ondo and Ekiti States. A descriptive research design was used for the study, two research hypotheses guided the study. The population of this study comprised 1,282 business education undergraduates from the universities in Ondo and Ekiti states. A proportionate sampling technique was used to arrive at 642 business education undergraduates as a sample. The questionnaire was the instrument used; linear regression was used for the hypotheses at 0.05 level of significance. It was revealed that self-efficacy and risk-taking propensity significantly influenced the entrepreneurial intention of business education undergraduates (B = 0.58, t(640) = 13.13, P = 0.000 and B = 0.42; t(640) = 11.85, P = 0.000). The study concludes that by focusing on these psychological traits within educational frameworks, institutions can better prepare students to engage in entrepreneurial activities. It was recommended that self-efficacy must be developed by helping students build confidence in their abilities through achievable goals and successes. Also, undergraduates should be taught to embrace challenges and view failures as learning opportunities.